Discourse on Religious Moderation in Public Space (Study on Friday Sermon Material of Nur Muhammad Mosque) - Ibah Turohmah; Ihwan Amalih (Penerbit Hellow Pustaka, 2025)
Religious moderation initiated by the Ministry of Religion of the Republic of Indonesia must now be developed because it is a solution to the problem of increasing religious extremism. Lastly, the radicalization of religious names in Indonesia has created a national security crisis which has attracted special attention from the government in its efforts to resolve it. It is necessary to understand the teachings of religious moderation to avoid conflict. Apart from that, it requires a public space that is very close and closely related to humans so that it can be easily conveyed. Therefore, this research will focus on the discourse of religious moderation in public spaces in the Friday sermon material at the Nur Muhammad Mosque which is seen as affiliated with HTI and FPI which have been disbanded by the government. In examining the focus of the research, researchers used qualitative field methods. As for the techniques used in data collection, researchers used observation, interviews and documentation methods. Researchers conducted interviews with several congregants and administrators of the Nur Muhammad Mosque, then checked by triangulating sources. The results of this research found that the values of religious moderation contained in the Friday sermon material at the Nur Muhammad Mosque are in the I'tida>l aspect such as exercising rights and fulfilling obligations, increasing devotion, being fair in leading. Furthermore, in the aspect of Tawa>zun, such as being balanced in all aspects of the world and the hereafter, entering Islam with kaffah, and understanding religion in depth. And in the aspect of Tasa>muh (Tolerance) such as caring for others, especially Muslims. The congregation's response to the values of religious moderation in the Friday sermon material at the Nur Muhammad Mosque, as in I'tida>l, is always to increase their devotion to deepening their religion and carrying out their obligations as Muslims, and not being biased in one way. Then in Tawa>zun, the congregation implements a balanced life by carrying out their obligations as servants of Allah and caliphs on earth. And in terms of Tasa>muh, the congregation always cares about those around them, does not easily blame, respects other people, and understands or does not intimidate those who are different from us.